Pengaruh Pemberian Ekstrak Etil Asetat Ulva fasciatadelile dan Turbinaria decurrensbory terhadap Laju Pertumbuhan Tumor Kelenjar Susu Padamencit C3h - Thamrin Wikanta; Vita Fitria Handayani; Lestari Rahayu; Asri Pratitis; Puspita Eka Wuyung (Balai Besar Riset Pengolahan Produk dan Bioteknologi Kelautan dan Perikanan, 2011)
ABSTRACTBreast cancer is the second mostly found disease after cervix cancer to Indonesian woman. Research on the effect of Ulva fasciata Delile and Turbinaria decurrensBory ethyl acetate extract feeding on the Adenocarcinoma mammaecell proliferation on C3H mice has beenconducted. Thirty experimental mice were devided into 6 treatment groups, i.e.: K-I, negative control; K-II, solvent control; K-III, given U. fasciata ethyl acetate extract dose of 41.32 mg/20 g BW (body weight); K-IV, given U. fasciataethyl acetate extract dose of 82.64 mg/20 g BW; K-V, given T. decurrensethyl acetate extract dose of 24.29 mg/20 g BW; and K-VI, given T. decurrens ethyl acetate extract dose of 48.59 mg/20 g BW. All treatments were given during 21 days. The mice body weight and tumor volume were measured and collected subsequently at every two days. Tumor doubling time was calculated at the end of research. Results showed that there wasa highly tumor growth inhibition on the K-IV shown by the high doubling time value. Tumor growth inhibition decreased according to the sequence as follows: K-IV (U. fasciata dose of 82.64 mg/20g BW), K-V (T. decurrensdose of 24.29 mg/20 g BW), K-VI (T. decurrensdose of 48.59 mg/20 g BW) which equal to K-II (solvent control), K-III (U. fasciatadose of 41.32 mg/20 g BW), K-I(negative control).